Salivary biomarkers of stress among teachers in an urban setting - Masilamani, R.; Darus, A.; Ting, A.S.; Ali, R.; Mahmud, A.B.A.; David, K. (SAGE Publications, 2011)
The aim of this study was to determine the prevalence of job stress among secondary school teachers using Karasek Job Content Questionnaire (JCQ), the association between salivary cortisol, salivary IgA, and sociodemographic characteristics, and the association between log cortisol, IgA levels, and job strain categories. A cross-sectional study was undertaken using JCQ and salivary cortisol and IgA samples. Cluster sampling was done yielding 302 respondents. The prevalence of stress among all teachers was 20.2. Being a Malay, teaching experience of 5 to 10 years, and those without a supervisor's support had higher prevalence of high job strain. Teachers in the 31 to 40 years age bracket, educating handicapped children with the absence of supervisor support exhibited higher stress levels with lower log salivary IgA levels. Further studies must be conducted using salivary biomarkers to study the in-depth relationship of stress, extending into other occupational groups.